Podcast-Based History of Indonesia Revolution Learning in Secondary Education - Fathoni, Zaenal (Indonesian Journal of History Education, 2023)
The objectives of this study are to: (1) Analyse and describe historical learning media that have been used for revolution material upholding the banner of the Republic of Indonesia in class XI at SMA 3 Semarang (a Senior High School); (2) Describe how the planning and development of podcast-based historical learning media for revolution material upholds the banner of the Republic of Indonesia; (3) Analyse the feasibility of using podcast-based historical learning media for revolution material upholding the banner of the Republic of Indonesia. This research conduct with Research and Development using a 4D development model from S. Thiagarajan, Dorothy Semmel, and Melvyn I Semmel Jerold which was modified by researchers which includes the stages of Define, Design, and Development. Media that teachers often use: power point, concept maps, and infographics. These learning media have weaknesses in the difficulty of students to review the material and understand historical events as a whole and chronologically because it only contains important points of the material. The results of this study show that podcast-based historical learning media for revolution material upholding the banner of the Republic of Indonesia is suitable for use in learning. This product received a rating of 98.07% from material experts, 87.5 from media experts, and 95.83% from practitioners. All assessments fall into the category of excellent and worthy of use in history learning in the classroom. Then strengthened by the results of product trials in the sample class through learning evaluation activities, students' understanding of the material in the podcast got an average score of 84.5% (Minimum Criteria is 75%).